Implementasi E-Government Berbasis Website Integrated Billing System (IBS) PT Pelabuhan Tanjung Priok - Berlian Rahmah Dewanto; Hudi Santoso (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
PT Pelabuhan Tanjung Priok has implemented a website-based e-government system through the Integrated Billing System (IBS) to enhance the effectiveness of public information services. This study aims to analyze the implementation of e-government in public information services through a website-based system using Indrajit's three elements of success theory, namely support, capacity, and value. The support element encompasses management commitment and policies toward digital service development; capacity relates to the readiness of human resources and technological infrastructure; while value represents the impact or benefits received by the public and customers from the digital services. The research method employed is qualitative with a descriptive approach to obtain in-depth and specific understanding regarding the implementation of IBS as a digital public information service system. Data were collected through interviews, observations, literature reviews, and documentation. The findings indicate that the implementation of e-government through IBS has been aligned with Indrajit's theoretical framework; however, further optimization is still required in the capacity and value aspects to achieve more effective, efficient, and responsive public information services.